2013
DOI: 10.1017/s0021932013000497
|View full text |Cite
|
Sign up to set email alerts
|

Hiv/Aids Knowledge, Attitude and Practice Among Women in the Least and Most Hiv/Aids Affected Regions of Mainland Tanzania

Abstract: Among women in mainland Tanzania, Iringa region in the southern highlands has the highest HIV/AIDS prevalence rate while Arusha region in the north-east has the lowest prevalence rate. In a 2007/8 survey, Iringa's HIV rate for women was 18.6% versus 0.8% in Arusha. Using data from a survey of women aged 15-49 years conducted in 2009 by the Champion project of EngenderHealth, a comparison was made of HIV/AIDS knowledge, attitude and practice between women in Iringa and Arusha regions. It was found that women in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, the findings of this study, which indicate a higher likelihood of a positive attitude regarding HIV/AIDS among rural women and a lower likelihood of a positive attitude among never-married women, directly contradict the prevailing understanding based on previous research. Earlier studies have reported that urban and unmarried women tend to exhibit more favorable attitudes toward HIV/AIDS [45, 73]. The reasons for these conflicting associations are not entirely clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the findings of this study, which indicate a higher likelihood of a positive attitude regarding HIV/AIDS among rural women and a lower likelihood of a positive attitude among never-married women, directly contradict the prevailing understanding based on previous research. Earlier studies have reported that urban and unmarried women tend to exhibit more favorable attitudes toward HIV/AIDS [45, 73]. The reasons for these conflicting associations are not entirely clear.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of explanatory variables in this study occurred in three stages. Firstly, an extensive literature search was conducted across various databases to compile a list of variables considered in prior studies within LMICs [23,26,29,30,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. Secondly, the survey's dataset was examined to verify the availability of these variables.…”
Section: Explanatory Variablesmentioning
confidence: 99%